LARYNGEAL MYXOMA: ANECDOTAL CASE - O. A. Saprina; G. V. Ungiadze; M. A. Kropotov; A. R. Karseladze (Опухоли головы и шеи)
Myxoma is a benign tumor of connective tissue. Myxomas are located in all organs, but very rarely in the head and neck area; a few cases of their involvement have been reported in the world literature. According to the authors’ data, these tumors have demonstrated a benign clinical course with a recurring trend and they are associated with fibrous dysplasias. The paper presents a case of a laryngeal myxoma.